AI DRIVEN INNOVATIVE BUSINESS MODELS: STUDY OF WOMEN-OWNED MICRO-ENTERPRISES IN INDIA - Shimpi, Leena Sharad; Srivastava, Saksham Kumar; Srivastava, Raman; Awasthi, Aishwarya; Mishra, Vanshita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Fostering entrepreneurship, women empowerment and innovation in small business has been key focus in the recent times. With adoption of artificial intelligence (AI)-driven business models, the success stories of AI driven business models have surfaced recently. These businesses are not only examples of innovation and empowerment, they are also sustainable. Present study had adopted a qualitative, exploratory multiple-case study methodology. Each AI driven business model, selected for the present study, employs context-specific AI tools—from predictive diagnostics and performance analytics to ethical data labor platforms—creating scalable, inclusive, and economically empowering solutions. Notably, in India, these models are equipping rural women with digital tools, financial access, and skill development, thereby generating employment, enhancing public health, and enabling community-based education and sports enterprises. The results of this study also highlight that how AI-driven innovation, when ethically and locally applied, can foster resilient, grassroots entrepreneurship among women.